Mucins in the colorectal neoplastic spectrum with reference to conventional and serrated adenomas - Sibel PERÇİNEL; Berna SAVAŞ; Arzu ENSARİ; Işınsu KUZU; M. Ayhan KUZU; Mehmet BEKTAŞ; Hülya ÇETİNKAYA; Nazmiye KURŞUN (Turkish Journal of Gastroenterology, 2019)
-